Corporate governance mechanisms and earnings management: The moderating role of female directors - Emmanuel Mensah; Christopher Boachie (Cogent Business & Management, 2023)
The current study investigates how board gender diversity moderates the relationship between corporate governance mechanisms (CG) and earnings management (EM) practices of firms in sub-Saharan Africa. The study samples annual reports and financial statements of 52 firms from nine sub-Saharan African countries over a period of 2007 to 2019 giving a total of 676 observations. Panel data models are used in the analyses. The study finds that, board gender diversity matters and significantly moderates the relationship between CG and EM practices of firms in sub-Saharan Africa. The findings of the study support the agency theory proposition that the constraining effect of firms' EM practices may be contingent on CG systems, particularly board gender diversity. The current study is the first African multi-cross-country study to introduce gender diversity as a moderating variable in the CG-EM nexus, thus extending the agency theory. It further contributes to the emergent advocacy for competent female representation on corporate boards so as to benefit from their essential characteristics and skills that drive their superior monitoring abilities, including EM monitoring.
Keywords: C38; G34; C33; G30; M41; 650; board gender diversity; earnings management; sub-Saharan Africa; corporate governance mechanisms; firm-performance; panel data models